Review of preclinical data of PF-07304814 and its active metabolite derivatives against SARS-CoV-2 infection - Chen, Wujun; Shao, Yingchun; Peng, Xiaojin; Liang, Bing; Xu, Jiazhen; Xing, Dongming (Frontiers in Pharmacology, 2022)
Main protease (Mpro) is a superior target for anti-SARS-COV-2 drugs. PF-07304814 is a phosphate ester prodrug of PF-00835231 that is rapidly metabolized into the active metabolite PF-00835231 by alkaline phosphatase (ALP) and then suppresses SARS-CoV-2 replication by inhibiting Mpro. PF-07304814 increased the bioavailability of PF-00835231 by enhancing plasma protein binding (PPB). P-glycoprotein (P-gp) inhibitors and cytochrome P450 3A (CYP3A) inhibitors increased the efficacy of PF-00835231 by suppressing its efflux from target cells and metabolism, respectively. The life cycle of SARS-CoV-2 is approximately 4 h. The mechanisms and efficacy outcomes of PF-00835231 occur simultaneously. PF-00835231 can inhibit not only cell infection (such as Vero E6, 293T, Huh-7.5, HeLa+angiotensin-converting enzyme 2 (ACE2), A549+ACE2, and MRC-5) but also the human respiratory epithelial organ model and animal model infection. PF-07304814 exhibits a short terminal elimination half-life and is cleared primarily through renal elimination. There were no significant adverse effects of PF-07304814 administration in rats. Therefore, PF-07304814 exhibits good tolerability, pharmacology, pharmacodynamics, pharmacokinetics, and safety in preclinical trials. However, the Phase 1 data of PF-07304814 were not released. The Phase 2/3 trial of PF-07304814 was also suspended. Interestingly, the antiviral activities of PF-00835231 derivatives (compounds 5-22) are higher than, similar to, or slightly weaker than those of PF-00835231. In particular, compound 22 exhibited the highest potency and had good safety and stability. However, the low solubility of compound 22 limits its clinical application. Prodrugs, nanotechnology and salt form drugs may solve this problem. In this review, we focus on the preclinical data of PF-07304814 and its active metabolite derivatives to hopefully provide knowledge for researchers to study SARS-CoV-2 infection.